Innovative self-adaptive gripper design, functional simulation, and testing prototype. (19th August 2022) - Frincu, Cezar Ioan; Stroe, Ioan; Staretu, Ionel
This article presents the design, functional simulation, and prototype of an innovative adaptive jaw gripper. First, based on the comparative analysis of several types of anthropomorphic finger grippers and adaptive jaw grippers, to avoid their disadvantages, the structural scheme of a gripper module based on a polycontour mechanism, comprising a guided parallelogram contour, was established to obtain a parallel translational movement of the elements of the jaw holders and therefore of the jaws. Then the structural analysis is briefly made to verify the correct operation of the mechanism of the gripping module, and details of the kinematic analysis and of the design of the components in the CATIA software are given. After obtaining the 3D version of the gripping module, its functional simulation and ADAMS analysis is performed. The sensory system used at the level of the jaws is also described and then the gripper assembly is obtained including a base plate and five gripper modules and as a result an adaptive gripper with five jaw holder elements is created. Next is the functional simulation of the adaptive gripper for gripping several types of parts. The prototype made and the test are presented for gripping five types of parts and we show the prospects of continuing this research with practical applicability by mounting on a robot and implementing in a robotic line for gripping and handling a series of parts of various shapes and sizes.